Design and Development of Hybrid Wind and Solar Energy System for Power Generation. (2018) - Prashanth, B.N.; Pramod, R.; Kumar, G.B. Veeresh
Abstract: People have harvested energy from the wind for quite a long time. Sails for boats, windmills for crushing grain or pumping water are a couple of illustrations. There is recharged intrigue now in energy harvesting from the wind, since it offers a contamination free method for producing power on a huge scale. The framework that fulfils the transformation of wind energy to power is known as a wind turbine. Presently a-days power is turning out to be rare. So in future, the renewable assets will be utilized to produce power. Indeed, even these days, 5% to 10% of the power is produced from wind and solar. In the meantime, every single work of the person is computerized by machines however the power generation is not up to the level. Above being the case, a hybrid wind and solar energy system was developed for the generation of power. The model is a combination of both horizontal axis wind turbine and solar panels where the blades of the wind turbine are being made by PVC pipes and the solar panel tiles are fitted along with the turbine blades. The project describes the modelling of two emerging electricity systems based on renewable energy: photovoltaic and wind power. The powers produced from both the sources were combined together using a Charge controller and then connected to an inverter. Finally, this power was fed to the residential load. The prototype exhibits an assessment of joined solar and wind system for house hold prerequisites, for example, lighting, fan, and so on. Moreover, wind turbine can be operated at lower wind speeds thus increasing the efficiency of the total system. The developed model of wind turbine was worked for the review to fulfill the vitality necessities on the houses. This model was tried alongside photovoltaic boards to check the power yield and the proficiency of the aggregate plan. A comparison between the suggested system and the proposed system proved that the proposed system had many advantages over the conversional system. The performance of the wind turbine was improved during the production process. At the point when the turbine is utilized with photovoltaic boards, the execution was enhanced fundamentally.